Enhanced shape anisotropy and magneto-optical birefringence by high energy ball milling in NixFe1-xFe2O4 ferrofluids - Nair, Swapna S.; Xavier, Francis; Joy, Pattayil Alias; Kulkarni, S. D.; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2008)
Ferrofluids belonging to the series NixFe1-xFe2O4 were synthesised by two different procedures-one by standard co-precipitation techniques, the other by co-precipitation for synthesis of particles and dispersion aided by high-energy ball milling with a view to understand the effect of strain and size anisotropy on the magneto-optical properties of ferrofluids. The birefringence measurements were carried out using a standard ellipsometer. The birefringence signal obtained for chemically synthesised samples was satisfactorily fitted to the standard second Langevin function. The ball-milled ferrofluids showed a deviation and their birefringence was enhanced by an order. This large enhancement in the birefringence value cannot be attributed to the increase in grain size of the samples, considering that the grain sizes of sample synthesised by both modes are comparable; instead, it can be attributed to the lattice strain-induced shape anisotropy(oblation) arising from the high-energy ball-milling process. Thus magnetic-optical (MO) signals can be tuned by ball-milling process, which can find potential applications. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: birefringence; Co-precipitation; ferrofluid; HEBM

Effect of cation distribution on structural and magnetic properties of Dy substituted magnesium ferrite - Bamzai, K. K.; Kour, Gurbinder; Kaur, Balwinder; Kulkarni, S. D. (Journal of Magnetism and Magnetic Materials, 2013)
Magnesium ferrite and dysprosium (Dy3+) substituted with composition MgDyxFe2-xO4 (x = 0.00-0.07) was prepared by solid state reaction technique. Spinel phase formation was identified using x-ray diffraction technique, thus establishing the cubic spinel symmetry. The morphology was seen through scanning electron microscopic technique, from where the grain size was calculated using average intercept line method. The elemental composition of pure and dysprosium substituted magnesium ferrite was calculated from energy dispersive x-ray analysis spectrum which is then correlated with the experimentally obtained values. Magnetic hysteresis loop of the various compositions establishes it to be soft ferrimagnetic material. The magnetic parameters such as saturation magnetization, coercivity, and retentivity were also calculated. Temperature dependence of saturation magnetization was done to find the Curie temperature of different compositions. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cation distribution; Curie temperature; Electron microscopy; Magnetization; Spinel ferrite